Epidemiology and Predictors of NTM Pulmonary Infection in Taiwan - a Retrospective, Five-Year Multicenter Study. Issue 1 (December 2017) - Huang, Hung-Ling; Cheng, Meng-Hsuan; Lu, Po-Liang; Shu, Chin-Chung; Wang, Jann-Yuan; Wang, Jann-Tay; Chong, Inn-Wen; Lee, Li-Na
Abstract Multicenter, longitudinal studies on nontuberculous mycobacteria (NTM) pulmonary infection (PI) are lacking. This study provides a 5-year epidemiological overview of NTM-PI in Taiwan and investigated its predictors. The clinical relevance of each respiratory NTM isolate in six hospitals between 2008 and 2014 was determined according to current guidelines. Recurrent episodes were judged by serial bacteriological results. New episodes of NTM-PI and pulmonary colonization (PC) occurring since 2010 were analyzed. Logistic regression analysis was performed to identify the predictors of NTM-PI. Between 2010 and 2014, the incidence rate of NTM-PI was 46.0 episodes per 100, 000 hospital-based patient-years.Mycobacterium avium intracellulare complex (MAC) was predominant in Northern Taiwan, whereas MAC andM. abscessus were copredominant in Southern Taiwan. Multiple episodes occurred in 9.5% of NTM-PI patients. No female predominance was observed, except for MAC-PI. Previous pulmonary tuberculosis and chronic obstructive pulmonary disease (COPD) were the most common pulmonary comorbidities and independent risk factors for NTM-PI. Other risk factors includedM. kansasii, M. abscessus, and southern Taiwan. Geographical variation of NTM-PI exists in Taiwan. Clinicians should keep a high suspicion on NTM-PI in the risk population. In endemic area of tuberculosis and COPD, there may be no female predominance in NTM-PI.